Information Technology in Agriculture - Singh, Manmohan (International Journal of Computer Sciences and Engineering, 2020)
Information Technology can improve the technologies used in farming and is very useful in farm management, crop data management. There is much contribution from Information Technology in agricultural productivity. Various technologies or Computer-aided devices are used in the agriculture sector that leads to growth and overall performance in any field such as horticulture, forestry, etc. Information Technology is not only useful at the farmer level but also it supports the research related to this field and business that is running in the agriculture field like information to the Management level. This article covers the Information technology-based systems that are useful for the farmer community, mobile-based solutions, and Web-based services, automated systems, Agriculture database that may be useful for Scientific Research, Management Information System in Agriculture in India. In addition to it, Expert Systems, robots developed and designed especially for the agriculture sector, DSS (Decision Support System) in agriculture and its importance for Management level.